The Influence of Motivation, Leadership Style, and Work Discipline on PT HSJI Employee Performance During the Covid-19 Pandemic - Saputra, May Rian Eka; Basriman, Iman; Entas, Derinta; Sukwika, Tatan (Jurnal Ilmiah Sumber Daya Manusia, 2024)
This research analyzes the influence of motivation factors, leadership style, and work discipline on employee performance during the COVID-19 pandemic. This quantitative research uses primary data, namely through interviews and filling out questionnaires. The sample was determined using a purposive method with saturated sampling—Structural Equation Model (SEM) data analysis using SmartPLS (Partial Least Square). This research shows that motivation factors and leadership style can influence work discipline factors, with a moderate accuracy value of 28.7%. At the same time, motivation, leadership style, and work discipline have a high accuracy value on employee performance, namely 78.2%. In this research, motivation and work discipline partially influence employee performance, while leadership style does not influence work discipline and employee performance. Then, motivation and leadership styles intervening through work discipline do not affect employee performance. The conclusion is that during the COVID-19 pandemic, the performance of PT HSJI employees was influenced by motivation and work discipline factors, while leadership style did not affect performance. It shows that the higher the motivation and the better the work discipline, the employee performance will also increase. Then, the better and more appropriate the leadership style applied by the leader, the better the employee performance will be.